Effectiveness of SARS-CoV-2 vaccines against Omicron infection and severe events: a systematic review and meta-analysis of test-negative design studies - Song, Shangchen; Madewell, Zachary J.; Liu, Mingjin; Longini, Ira M.; Yang, Yang (Frontiers in Public Health, 2023)
Background A rapidly growing body was observed of literature evaluating the vaccine effectiveness (VE) against Omicron in test-negative design studies. Methods We systematically searched papers that evaluated VE of SARS-CoV-2 vaccines on PubMed, Web of Science, Cochrane Library, Google Scholar, Embase, Scopus, bioRxiv, and medRxiv published from November 26th, 2021, to June 27th, 2022 (full doses and the first booster), and to January 8th, 2023 (the second booster). The pooled VE against Omicron-associated infection and severe events were estimated. Results From 2,552 citations identified, 42 articles were included. The first booster provided stronger protection against Omicron than full doses alone, shown by VE estimates of 53.1% (95% CI: 48.0–57.8) vs. 28.6% (95% CI: 18.5–37.4) against infection and 82.5% (95% CI: 77.8–86.2) vs. 57.3% (95% CI: 48.5–64.7) against severe events. The second booster offered strong protection among adults within 60 days of vaccination against infection (VE=53.1%, 95% CI: 48.0–57.8) and severe events (VE=87.3% (95% CI: 75.5–93.4), comparable to the first booster with corresponding VE estimates of 59.9% against infection and 84.8% against severe events. The VE estimates of booster doses against severe events among adults sustained beyond 60 days, 77.6% (95% CI: 69.4–83.6) for first and 85.9% (95% CI: 80.3–89.9) for the second booster. The VE estimates against infection were less sustainable regardless of dose type. Pure mRNA vaccines provided comparable protection to partial mRNA vaccines, but both provided higher protection than non-mRNA vaccines. Conclusions One or two SARS-CoV-2 booster doses provide considerable protection against Omicron infection and substantial and sustainable protection against Omicron-induced severe clinical outcomes.